2009
DOI: 10.1088/1742-5468/2009/02/p02008
|View full text |Cite
|
Sign up to set email alerts
|

Effective pair potentials for spherical nanoparticles

Abstract: An effective description for spherical nanoparticles in a fluid of point particles is presented. The points inside the nanoparticles and the point particles are assumed to interact via spherically symmetric additive pair potentials, while the distribution of points inside the nanoparticles is taken to be spherically symmetric and smooth. The resulting effective pair interactions between a nanoparticle and a point particle, as well as between two nanoparticles, are then given by spherically symmetric potentials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The coarse-graining method provides the advantage of significantly reducing the number of interactions required and has been used to study gold nanoparticles 17 , spherical silica nanoparticles 19 , and generic spherical nanoparticles 18 . They either (i) model the entire cluster as a single coarse-grained entity or (ii) model the cluster as a rigid unit composed of atoms, interacting through general exponential or power-law potentials to describe the energetics of cluster-atom and atomic cluster-cluster pairs.…”
Section: Inter-cluster Atomic Pair-potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coarse-graining method provides the advantage of significantly reducing the number of interactions required and has been used to study gold nanoparticles 17 , spherical silica nanoparticles 19 , and generic spherical nanoparticles 18 . They either (i) model the entire cluster as a single coarse-grained entity or (ii) model the cluster as a rigid unit composed of atoms, interacting through general exponential or power-law potentials to describe the energetics of cluster-atom and atomic cluster-cluster pairs.…”
Section: Inter-cluster Atomic Pair-potentialsmentioning
confidence: 99%
“…Molecular dynamics studies of cluster systems 17,18 generally use one of two approaches to perform bulk simulations. They either (i) model the entire cluster as a single coarse-grained entity or (ii) model the cluster as a rigid unit composed of atoms, interacting through general exponential or powerlaw potentials to describe the energetics of cluster-atom and atomic cluster-cluster pairs.…”
Section: Inter-cluster Atomic Pair-potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to advances in synthetic techniques it is now possible to produce colloidal spheres of different chemical compositions that are monodisperse in size and can be modified by attaching the desired modifying groups on the surface of the colloid sphere [10,11]. It has been demonstrated that properties of these colloidal spheres can be further modified by coating them with thin shells of a different chemical composition, as well as varying thickness in a controllable way [12,13], and this modification is useful in tuning interactions between colloidal spheres [14]- [16]. In short, it is now not difficult to prepare synthetic particles with desired inter-particle interactions.…”
Section: Introductionmentioning
confidence: 99%